2020
DOI: 10.4103/1319-4534.322615
|View full text |Cite
|
Sign up to set email alerts
|

Supernumerary lacrimal puncta

Abstract: Supernumerary lacrimal punctum is rare, and very few cases have been reported. Most patients are asymptomatic, but in some excessive tearing could be a symptom. In addition, obstruction of the canaliculi causing canaliculitis has been reported. We describe four cases in detail with their presentations and diagnosis. The first patient presented with a right eye lesion and during examination, the left eye was less than mid dilated compared to that of the right eye. Further examination of the left eye revealed tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…suggested that the right lower lid is the most reported location for the occurrence of supernumerary puncta [ 1 , 6 ]. Thirty-nine patients out of the total 51 patients (76%) were found to have had right lower lid supernumerary puncta which is consistent with previous reports [ 1 , 3 , 5 - 14 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…suggested that the right lower lid is the most reported location for the occurrence of supernumerary puncta [ 1 , 6 ]. Thirty-nine patients out of the total 51 patients (76%) were found to have had right lower lid supernumerary puncta which is consistent with previous reports [ 1 , 3 , 5 - 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our case series of four patients showed similar trends, with all four having only double puncta on any one eyelid. It was also consistent with the comprehensive table results which demonstrated the vast majority of patients presenting with double puncta on any one eyelid (98%) and only one patient out of the 51 (2%) with triple puncta in an eyelid that only had intermittent epiphora and no interventions performed [ 1 , 3 , 5 - 14 ]. Forty-six percent of patients (n=23) in the table were reported by Satchi et al .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations